2012
DOI: 10.1210/jc.2012-2108
|View full text |Cite
|
Sign up to set email alerts
|

Higher Free Thyroxine Levels Predict Increased Incidence of Dementia in Older Men: The Health In Men Study

Abstract: Higher FT(4) levels predict new-onset dementia in older men, independently of conventional risk factors for cognitive decline. Additional studies are needed to explore potential underlying mechanisms and to clarify the utility of thyroid function testing in older men at risk of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 40 publications
3
63
2
1
Order By: Relevance
“…This may reflect reduced sensitivity of the pituitary to T 4 -or liothyronine (T 3 )-mediated suppression of TSH levels, altered TSH bioactivity or reduced thyroid sensitivity to TSH, requiring compensatory elevation of levels to maintain thyroid homeostasis (10). Small differences in thyroid function between euthyroid subjects have been reported to be associated with specific health-related outcomes including atrial fibrillation, reduced bone mineral density and incident dementia (12,13,14). However, the effect of differences in thyroid function in euthyroid older people on the key outcome of mortality remains unclear, with limited available data and inconsistent findings reported (11,15,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…This may reflect reduced sensitivity of the pituitary to T 4 -or liothyronine (T 3 )-mediated suppression of TSH levels, altered TSH bioactivity or reduced thyroid sensitivity to TSH, requiring compensatory elevation of levels to maintain thyroid homeostasis (10). Small differences in thyroid function between euthyroid subjects have been reported to be associated with specific health-related outcomes including atrial fibrillation, reduced bone mineral density and incident dementia (12,13,14). However, the effect of differences in thyroid function in euthyroid older people on the key outcome of mortality remains unclear, with limited available data and inconsistent findings reported (11,15,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the group of subjects seropositive for thyroid antibodies had a higher prevalence of abnormal serum TSH concentrations, this inverse correlation persisted after adjusting for TSH values and was therefore independent of TSH (69). A similar lack of association between TSH and frailty was reported in men also (among more than 3000 participants ≥70 years) (70). Simonsick et al showed that older individuals with elevated TSH levels do not demonstrate increased risk of mobility problems; rather, those with mild TSH elevation showed a slight functional advantage (71).…”
Section: Thyroid Status Morbidity and Mortality In The Elderlymentioning
confidence: 52%
“…In a cohort of 3485 euthyroid men aged 70-89 years from the Health In Men Study, higher FT4 levels were found to be associated with all-cause mortality, independently of conventional risk factors and medical comorbidities (76). Noteworthy, in the same cohort from the Health In Men Study, higher FT4 was an independent and significant predictor of frailty, suggesting that circulating FT4, even within the normal range, might contribute to weight loss and reduced physical capability (70). Similar findings had been reported by van den Beld et al who noted that in euthyroid men aged 73-94 years, higher serum FT4 concentrations were associated with reduced physical function, while low serum FT4 was associated with better 4-year survival (77).…”
Section: Thyroid Status Morbidity and Mortality In The Elderlymentioning
confidence: 98%
See 2 more Smart Citations